Study of sand brick ratio 1:6 for partial replacement of sand with palm oil clinker (7.5%, 12.5% and 17.5%) - Fakhriah Hanun, Mohamed Shah (2019)
The present research stems out from the environmental problem posed by dumping of palm oil clinker, a by-product of palm oil industry and excessive sand mining issues. Thus, experimental work has been conducted to investigate the effect of palm oil clinker content as partial sand replacement on the properties of brick. A total of three mixes containing various percentage of palm oil clinker, which are 7.5% 12.5% and 17.5% have been prepared. All specimens were water cured and air cured until the testing date. The compressive strength test, flexural strength test and water absorption test was conducted at 28 days, 60 days, and 90 days. The findings show that incorporation of 7.5 %, 12.5% and 17.5% palm oil clinker contribute towards densification of the mix which enhances compressive strength, flexural strength, density and water absorption rate test performance of the brick. The water absorption of the brick increases slightly when palm oil clinker is integrated as partial sand replacement. On overall, a good quality of brick can be produced by replacing sand with POC as in JKR Standard.